Study on the Fast Neutron Multiplicity Measurement of Uranium Material - Li, Sufen; Li, Kaile; Zhang, Quanhu; Cai, Xingfu (Frontiers in Energy Research, 2022)
As a non-destructive testing and analysis technology, the neutron multiplicity measurement method plays an important role in the field of arms control verification. Great progress has been achieved in the fast neutron multiplicity measurement of plutonium, while there are few studies that have been conducted in the fast neutron multiplicity measurement of uranium. In this study, a set of fast neutron multiplicity measurement devices based on the BC501A liquid scintillation detector was built, and two small mass uranium samples with low density were studied. It is found that the change of the total neutron counting rate is irregular, and the coincidence counting rate will increase linearly with the mass. It is due to the energy loss caused by the scatter of the Am-Li source neutron with the sample, resulting in part of the neutron energy below the threshold. A simulation detection system is built by Geant4 to verify the reliability. On this basis, four kinds of packaging materials such as steel, copper, aluminum, and graphite were studied. The measurement results of different materials were compared and analyzed. The thickness of the material was studied, and the functional relationship curve was fitted. In this study, the fast neutron multiplicity measurement of small-mass and low-density uranium samples was carried out and verified. The influence of different packaging materials on the multiplicity measurement was analyzed, which is of great significance for the development of the fast neutron multiplicity measurement technology.